The Analysis of Factors Affecting Foreign Investment in Indonesia - Nur Cahyaningsih (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2015)
Foreign Direct Investment (FDI) has important role in Indonesian economic development and becomes the engine of growth for the economy. For all this reason, the government starts doing promotions attracting foreign investors to invest in Indonesia by issuing a number of policies. In fact, some foreign companies have left from Indonesia. This research aims at determining the effect of GDP, inflation, and infrastructure toward Foreign Direct Investment in Indonesia from 1981 until 2014. It uses time series data and Error Correction Model (ECM) as the method. Based on analysis findings, all variables used by stationary in first difference, dependent and independent variables in the equation of co-integrating regression has long-term relationship. In the short term, GDP and Infrastructure do not have a significant influence, while inflation has a negative influence and significant in α 5% toward Foreign Direct Investment. In the long term, GDP and Infrastructure have a positive effect and significant at α 5%, while inflation does not have a significant influence to Foreign Direct Investment in Indonesia.